Revenue Mobilization and Investment on Infrastructure of Local Governments in Nigeria (American International Journal of Economics and Finance Research, 2019)
This thesis examined the effects of revenue mobilization and investment of local governments in Nigeria. Secondary data were collected from Central Bank of Nigeria Statistical Bulletin. The dependent variables were proxy by value of basic amenities and value of infrastructural development. The independent variables were proxy by federal government allocation, state government allocation, value added tax, internally generated revenue and grants. Descriptive statistics and multiple regressions were used to examine dynamic long run relationship that exists between revenue mobilization and local government development. Ordinary Least Square (OLS), Augmented Dickey Fuller Test, Johansen Co-integration test, normalized co-integrating equations, parsimonious vector error correction model and pair-wise causality tests were used. The estimated model revealed that value added tax, state allocation, grants and federal allocation have positive effect on value of infrastructural development while internationally generated revenue have negative effect on infrastructural development. The unit root result (ADF) showed that the variables were stationary at the first difference of Order 1 (1). The co-integration tests revealed a long run dynamic relationship between the dependent and independent variables in the models. The parsimonious model summary shows that revenue mobilization explains positive and significant relationship between the revenue and development of local government. However, the direction of causality between revenue and development is mixed indicating uni and bi-directional causality. The study concluded that local government revenue has significant effect on infrastructural investment of Nigeria local governments. Its recommends policies should be directed toward effective utilization of revenue and local government finance should manage in line with international best practices.